MANAJEMEN PEMBELAJARAN PENDIDIKAN ISLAM MODERAT DI PERGURUAN TINGGI ISLAM (Studi Atas Institute Agama Islam Negeri Madura) - Mohammad Muchlis Solichin (Prodi MPI Fakultas Tarbiyah IAIN Madura, 2018)
The purpose of this paper is to understand: 1) learning planning of moderate Islam education in the State Islamic Institute Madura 2) learning implementation of moderate Islamic education in the State Islamic Institute Madura and 3) learning evaluation of moderate Islamic education in the State Islamic Institute of Madura. The method used is qualitative descriptive. Methods of data collection are observation, interviews, and documentation. Analysis of the data used is: data reduction, data display, and conclusions. The results showed that: 1) learning planning of moderate Islamic education do with the preparation of syllabus and Implementation lesson Plan. 2) learning implementation of moderate Islamic educatio is a teaching strategy that is used is a discussion/debate on and problem-based learning. Meanwhile, the learning materials of moderate Islamic education containes the subjects as follow: the al- Qur'an, the History Islamic Culture, Psychology of Religion, Education of Akhlaq Tasawwuf. Philosophy of Islamic Education and Islamic philosophy. While the themes of discussion include: democracy, human rights, tolerance of differences. Further, learning evaluation of moderates Islamic education in IAIN Madura is sustainable.